Monitoring mammals in the Caxiuanã National Forest, Brazil – First results from the Tropical Ecology, Assessment and Monitoring (TEAM) program. - Martins, Simone de Souza (Springer, 2010)
The need for long-term biodiversity monitoring using standardized protocols led to the creation of the Tropical Ecology, Assessment and Monitoring (TEAM) initiative. At some 50 field stations in tropical forests around the world, TEAM will monitor various taxa such as ants, birds, butterflies, medium and large terrestrial mammals, primates, litter fall, and trees, as well as landscape change in nine tropical biodiversity hotspots and three tropical wilderness areas. The TEAM terrestrial mammal program calls for using a grid of camera phototraps to monitor long-term trends in densities and occupancy rates of species that can or cannot be uniquely identified, respectively. We describe the TEAM camera phototrapping program and provide results for the first TEAM site–Caxiuana˜ National Forest in northern Brazil. An intensive one year camera trapping effort was carried out to determine which months were most suitable for long-term monitoring. Fifteen species of medium and large terrestrial mammals and two large birds were recorded, including three xenarthrans, five carnivores, one perissodactyle, three artiodactyles, two rodents, and one marsupial. The medium and large terrestrial mammal diversity was well represented during two consecutive wet and dry months, respectively. We also recorded activity patterns for all species photographed by our camera traps more than 10 times.